(untitled) (World Bulletin of Management and Law, 2023)
This article reveals the social significance of legal entities, especially non-profit organizations in civil law, which are formed as a result of unification of individuals without economic benefit. This means that the study of the legal status of non-profit organizations, the order of their organization and the legal basis of their activity requires the study of several branches of law at the same time